Interpretace textu v československé vzdělávací soustavě = The interpretation of a literary text in the czechoslovak educational system - Svobodova, Alena (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The purpose of the interpretation of a text is the cultivation of aesthetic feeling of man and the stimulation of the sensations, which make his life pleasant on the one hand, and that of the ability of expressing himself actively and on his own initialitive, being of great interest, nicely and adequately on the other hand.
Keywords: dydaktyka literatury; Czechosłowacja